Venous hypertension in syndromic and complex craniosynostosis: The abnormal anatomy of the jugular foramen and collaterals. Issue 3 (April 2015) - Florisson, Joyce M.G.; Barmpalios, Georgios; Lequin, Maarten; van Veelen, Marie-Lise C.; Bannink, Natalja; Hayward, Richard D.; Mathijssen, Irene M.J.
Abstract Why craniosynostosis patients develop elevated intracranial pressure (ICP) is still a mystery. Our aim was to investigate jugular foramen size and its relation to venous hypertension and elevated ICP. Secondly, we evaluated whether occipital collateral veins develop as a compensatory mechanism for elevated ICP. We conducted a prospective study in 41 children with craniosynostosis who underwent a 3D-CT-angiography. We evaluated the anatomical course of the jugular vein, the diameter of the jugular foramen and the relation to the presence of papilledema. Additionally, we studied the anatomical variations of the cerebral venous drainage system. The diameter of the jugular foramen was significantly smaller in our patients. Abnormal venous collaterals were most often observed in patients with Apert, Crouzon–Pfeiffer and Saethre–Chotzen syndrome, even in children under two years of age. There was no significant difference in the number of collateral veins in patients with or without papilledema. Collaterals appear to reflect an inborn abnormality of the venous system, rather than a compensating mechanism for elevated ICP. This study confirms the presence of jugular foraminal narrowing in craniosynostosis patients and an abnormal venous system, which may predispose to elevated ICP. Level of Evidence: Diagnostic II.